Antibacterial, Hemagglutination, and Insecticidal Activity Studies on the Solvent Extracts of the Roots of Olea ferruginea - Yaseen, Muhammad; Kamran, Muhammad; Farid, Arshad; Ismail, Salmah; Muzammal, Muhammad; Amir, Kamal Abdul; Khan, Muhammad Hashim; Ahmad, Sohail; Rashid, Sheikh Abdur (UI Scholars Hub, 2022)
Olea ferruginea has been used to treat skin ailments, as well as kidney and ocular problems for a long time. The current study was designed with the aim of investigating and scientifically validating its widespread use. Chloroform, n-hexane, and ethyl acetate were used to assess the antibacterial, hemagglutination, and insecticidal properties of O. ferruginea roots. Escherichia coli, Micrococcus luteus, Klebsiella pneumoniae, and Pseudomonas aeruginosa were among the bacterial strains selected for assessing antibacterial activity. The results showed that ethyl-acetate (EtOAc) extract (56%) and chloroform (CHCl3) extract (56%) showed the widest zone of inhibition against K. pneumonia, while n-hexane extract (13.4%) had the lowest zone of inhibition against P. aeruginosa. All three extracts remained inactive against M. luteus. During hemagglutination activity, the CHCl3 and EtOAc extracts, when used at different concentrations, only agglutinated the AB−ve and O+ve blood groups, respectively, while the n-hexane extract strongly agglutinated the A−ve and B−ve blood groups at different concentrations. The plant extracts were also checked for insecticidal activity against Rhizopertha dominica. The results also revealed the high mortality rate of CHCl3 extract (70%) against R. dominica as compared to other extracts. The aforesaid activities suggest that the roots of O. ferruginea have excellent medicinal viability and contain a wide variety of agglutinins and lectins, as shown in this study.